PERAN KADER POSYANDU DALAM UPAYA OPTIMALISASI PELAKSANAAN KELAS IBU BALITA DI WILAYAH KECAMATAN CURUP TIMUR KABUPATEN REJANG LEBONG BENGKULU - Wenny Indah Purnama Eka Sari; Yusniarita Yusniarita; Kurniyati Kurniyati; Eva Susanti; Farida Esmianti; Yossy Utario (GEMASSIKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
The strategy for reducing infant mortality rates (IMR) requires an integrated approach between community empowerment to increase access to education for mothers of infants and toddlers, one of which is a class for mothers of children under five. The success of the Mother Class Of Toddlers program is very dependent on the support and participation of the community. Health cadres have an important contribution to improving the community's ability to achieve optimal health status. Community service activities aim to train the skills of posyandu cadres as Toddler Class Cadres through the empowerment of posyandu cadres in optimizing the implementation of mother-to-five classes. The target of the activity is 15 active Posyandu Cadres in the Curup Timur District, Kepahiang Regency, Bengkulu. The average posttest score was 93.67 after the training, indicating there was an increase in the knowledge score of cadres. The average value of the skills of the toddler class cadres is 81.29. It means that almost all cadres have good knowledge and skills as toddler class cadres after training. Posyandu cadres have played an active role as Class Cadres for toddlers by managing toddler classes well when mentoring is going well.